Short Term Evolution of a Highly Transmissible Methicillin-Resistant Staphylococcus aureus Clone (ST228) in a Tertiary Care Hospital - Vogel, Valérie; Falquet, Laurent; Calderon-Copete, Sandra P.; Basset, Patrick; Blanc, Dominique S. (PLOS ONE, 2012)
Staphylococcus aureus is recognized as one of the major human pathogens and is by far one of the most common nosocomial organisms. The genetic basis for the emergence of highly epidemic strains remains mysterious. Studying the microevolution of the different clones of S. aureus is essential for identifying the forces driving pathogen emergence and spread. The aim of the present study was to determine the genetic changes characterizing a lineage belonging to the South German clone (ST228) that spread over ten years in a tertiary care hospital in Switzerland. For this reason, we compared the whole genome of eight isolates recovered between 2001 and 2008 at the Lausanne hospital. The genetic comparison of these isolates revealed that their genomes are extremely closely related. Yet, a few more important genetic changes, such as the replacement of a plasmid, the loss of large fragments of DNA, or the insertion of transposases, were observed. These transfers of mobile genetic elements shaped the evolution of the ST228 lineage that spread within the Lausanne hospital. Nevertheless, although the strains analyzed differed in their dynamics, we have not been able to link a particular genetic element with spreading success. Finally, the present study showed that new sequencing technologies improve considerably the quality and quantity of information obtained for a single strain; but this information is still difficult to interpret and important investments are required for the technology to become accessible for routine investigations.